CURIOSITY IN VERONICA ROTH’S DIVERGENT - Lempas, Rivaldo; Mogea, Tini; Maukar, Merlin M. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to determine the curiosity aspect in Veronica Roth’s Divergent, focused on the main character, Beatrice “Tris” Prior. This study categorized as qualitative research with objective approach since the data was collected in the forms of words, quotations from the novel and some other sources that support the study. The writer also focused solely on the novel and the internal elements of the novel itself in analyzing this study. The result of this study showed that the main character’s challenges and questions could all be solved as a result of her curiousness. It can be seen as: Curiosity of the Faction System, showed that the purpose of Faction had changed and no longer to make people live in harmony and protect them from killing each other; Curiosity in Dauntless and Divergence, showed that Dauntless were indeed trained to eliminate Divergents, as they were seen as threat and rebels; Curiosity in Taking Risk, showed how Tris’s curiousness and her acts of doing things without even consider the risks could actually revealed the truth on the questions she often aksed herself; Curiosity in Survival, showed how Tris’s curiousness and instinct of survival could save her; and Curiosity in Dangerous Situation, showed how Tris’s managed to passed plenty of dangerous situations were also caused by her curiousness